The triple overlap of COPD, severe obesity, and high risk of OSA: insights from an NHANES analysis - Staci L. Orbell; Jonna L. Morris; Paul W. Scott; Lynn M. Baniak; Christopher C. Imes; Bomin Jeon; Weiwen Wang; Yue Dong; Patrick J. Strollo; Faith S. Luyster (BMC Pulmonary Medicine)
Abstract Purpose With the rising prevalence of severe obesity, the coexistence of obstructive sleep apnea (OSA) and chronic obstructive pulmonary disease (COPD) often progresses to triple overlap syndrome, a condition with significant health implications. However, its prevalence remains poorly understood. Using population-based data from the National Health and Nutrition Examination Survey (NHANES), we examined the prevalence of triple overlap of COPD, severe obesity, and high risk for OSA (HR-OSA) and associated sociodemographic factors among US adults. Methods A cross-sectional analysis was performed using NHANES data between 2005 and 2008 and 2015-March 2020. COPD diagnosis was collected via self-report questionnaire. HR-OSA was determined by an adapted Multivariable Apnea Prediction index. Severe obesity was defined as a body mass index of ≥ 40.0 kg/m2. Results From 2005 to 2008 to 2015-March 2020, the proportion of participants with triple overlap of COPD, severe obesity, and HR-OSA increased from 0.653% (95% CI, 0.651-0.655%) to 1.560% (95% CI, 1.557-1.563%). During the same period, the increase in the age-standardized prevalence of severe obesity (from 6.298% [95% CI, 6.291-6.305%] to 8.943% [95% CI, 8.936-8.950%]) and HR-OSA (from 58.667% [95% CI, 58.646-58.688%] to 58.776% [95% CI, 58.758–58.794%]; ) exceeded the increase for COPD (from 9.223% [95% CI, 9.215-9.231%] to 10.213% [95% CI, 10.206-10.220%]). Women and those with low family income were more likely to have triple overlap of COPD, severe obesity, and HR- OSA. Conclusion The triple overlap of COPD, severe obesity, and HR-OSA significantly increased among US adults over the past 15 years, with disparities across different sociodemographic groups. Trial registration : Not applicable.